A Rádio-peão no ar Um estudo sobre a comunicação informal e a comunicação formal face a face no ambiente organizacional - Perez, Katia (2010)
The organizational grapevine has been studied since the World War II in the United States. In Brazil, this communication process has gained prominence in late 1970 with the labor movements looking for democratic forms of communication during the military regime. The formal face-to-face communication began to be practiced in organizations in the mid-1990s with the arrival of new models of international business management. Based on the study of both grapevine and formal face-to-face communication, by bibliographic research and in-depth interviews with academics and professionals from different fields of knowledge, it was possible to describe their histories, attributes and roles in organizations nowadays, and how these two forms of face-to-face communication (formal and informal) interact with each other, according to personal or organizational interests.(AU)